Dialogical Interplay and the Drama of Harold Pinter - Boulter, Stuart Jonathan (My University, 1992)
The thesis is an effort to understand the way in which three of Pinter's early plays, The Birthday Party, A Slight Ache, and Tea Party are structured to work precise effects upon audiences. The underlying premise of this work is that Pinter compels his audience to assume an active role in the unfolding drama by manipulating the distance between audience and play. The activity of the audience can be understood to comprise two components. When confronted by the myriad questions posed by the Pinter play the audience begins to pose its own questions and to attempt to fix its own totalizing structures upon the play. I call this primary position of the audience its posture of hermeneutical inquiry. The second phase of the audience's participation in the play begins as the spectator notices that his or her own interpretive process is exactly analogous to that of the major characters in the drama. Any firm distinction in the ontological status of spectator and character is blurred. I have termed this blur "dialogical interplay": Pinter manipulates his audience to direct questions not only at the play, but to pose questions within the play itself.
What is crucial to note, however, is that in all cases of the plays under scrutiny here, the character who shares the posture of the spectator (and in this sense "becomes" the spectator) is destroyed, either physically or mentally. Thus the experience of the Pinter play is one which invariably involves the audience's sense of its own violation. Ultimately, I contend that the audience's proximity to the dramatic proceedings is encouraged because of Pinter's overriding sense of contempt for his audience, yet it is precisely the audience's sense of imminent danger that can account in part for the hold Pinter's plays have had over the decades.
Keywords: English Language and Literature; English Language and Literature